Elaboración de una guía pedagógica sobre inclusión educativa dirigida a los padres de familia de hijos con capacidades diferentes de la escuela “Juan Pio Montufar Y Juan De Dios Morales De La Parroquia Mulaló Cantón Latacunga Provincia Del Cotopaxi” año lectivo 2012- 2013 - Jácome Quinatoa, Jorge Patricio (2013)
The present research has as a goal to design a pedagogic guide about inclusion educative which will allow parents have an adequate knowledge about how they should treat their children with different capacities at Juan Pío Montufar and Juan de Dios Morales school. Disabled children have a restriction or lack of results when they do any activity in a normal form. These deficiencies of abilities are consequences of illness which are responsible of affecting the students’ academic performance. This study is the descriptive type therefore it was used the interview and the survey as the techniques; these helped to obtain real data as a result of the analysis and interpretation of the information obtained which was represented in graphics and charts, essential basis on which the design of the proposal was presented .This proposal is the answer to this matter developed with scientific, analytic and synthetic methods. Through the results it was possible to observe there is low performance of disabled children. The objective of the proposal is to provide some instruments which facilitate the teaching learning process for benefiting the institution and children to improve their self-esteem taking into account the acceptance of their disabilities and achieving an educative insertion with the same opportunities, an excellent education and respecting their rights.